Validity of different EMG analysis methods to identify aerobic and anaerobic thresholds in speed skaters - Piucco, T.; Diefenthaeler, F.; Prosser, A.; Bini, R. (Journal of Electromyography and Kinesiology, 2020)
This study aimed to assess the validity of the first (EMGth1) and second (EMGth2) breakpoints in the EMG signal during skating. Scope: Ten well-trained long track speed skaters performed a maximal incremental skating test on a slide board. EMG signals from six lower limb muscles were recorded during the last 15s of each stage and converted to Root Mean Square for determination EMGth1 and EMGth2 using mathematical (2 and 3 linear regressions) and visual methods. Conclusions: EMGth1 had a low detection rate (less than 50%) while EMGth2 could be identified visually in >80% of cases, in 85% of cases using 2-lines and 63% using 3-lines regression. Quads (VL + VM) and Gluts (GM + GMd) had the highest EMGth2 detection rate for all methods (>70%). EMGth2 from Quads and Gluts detected by the 2-lines and 3-lines regression were not different than the second ventilatory threshold (VT2) (p>0.05), while the visual method overestimated VT2 (p<0.01). EMGth2 detected from Quads by the 2-lines regression method presented better correlation with VT2 stage (r=0.91), lowest bias, and limit of agreement. We conclude that EMG is a valid non-invasive method to detect VT2 during skating when using a mathematical method to determine EMGth2.